2020
DOI: 10.1002/nop2.519
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation in nursing interventions—A review of the literature

Abstract: Aim To identify and synthesize qualitative evaluation methods used in nursing interventions. Design A systematic qualitative review with a content analysis. Four databases were used: MEDLINE, PsycINFO, Embase and CINAHL using pre‐defined terms. The included papers were published from 2014–2018. Methods We followed the guidelines of Dixon‐Woods et al., Sandelowski and Barroso, the Critical Appraisal Skills Programme qualitative checklist and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…patient‐centred handover practices) and designing interventions to address these. Qualitative evaluation is recognized as a way of evaluating the implementation of nursing interventions and improvements, particularly when interventions occur in natural settings (Rørtveit et al, 2020 ). Previous research on communication in hospital emergency departments (Pun et al, 2017 ; Slade et al, 2015 ) and clinical handover (Eggins et al, 2016 ) has demonstrated the effectiveness of our approach.…”
Section: The Studymentioning
confidence: 99%
“…patient‐centred handover practices) and designing interventions to address these. Qualitative evaluation is recognized as a way of evaluating the implementation of nursing interventions and improvements, particularly when interventions occur in natural settings (Rørtveit et al, 2020 ). Previous research on communication in hospital emergency departments (Pun et al, 2017 ; Slade et al, 2015 ) and clinical handover (Eggins et al, 2016 ) has demonstrated the effectiveness of our approach.…”
Section: The Studymentioning
confidence: 99%
“…For this reason, our study cannot be considered representative, which is a limitation. However, small scale studies are important as a means of evaluating naturalistic setting [52] or bridging gaps between research and practice [53]. From this perspective, our study provides information about how to conceptualise therapeutic writing for patients suffering from BED as experienced in a group setting.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The aim of a project titled 'Quality End-of-life Care' (QEoLC) described in this paper is to pilot evidence-based approaches to improve the quality of palliative and end-of-life care for older people in Australian RACHs. A qualitative evaluation of the intervention was conducted because it allows researchers to gain a thorough and in-depth understanding of participants' perspectives, which can greatly assist with understanding pros and cons of different components of the intervention (Rørtveit et al, 2020) and in improving care. Furthermore, the results highlight the need for codesigning the intervention with RACHs, provision of dedicated staff/resources to support implementation, and integration of project tools with existing systems for achieving effective implementation outcomes.…”
Section: Introductionmentioning
confidence: 99%